Determination of Malondialdehyde (MDA) Levels In The Saliva of Man Smokers Age 45 - 59 Years - Dhina Lorenza; Harliansyah Harliansyah (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Smoking can cause health problems. In elderly smoking has become a habit in continuing the previous habit, even smoking habit tends to simply continue without the accompaniment of strong reasons, and these habits become addictive. Riskesdas research results showed that 65.6% of men smoked in 2007 and other research showed that 67% of men smoked in 2011, the prevalence of smoking continues to increase both men and women. Cigarette smoke can cause oxidative stress which is characterized by increased levels of MDA (malondialdehyde) as a marker of oxidative stress in the cell membrane. Objective: This study aimed to determine the effect of smoking on salivary MDA levels in smokers aged 45-59 years. Methods: The study was descriptive cross sectional analytic. The primary data used in this study. Determination of the population in the sample using quota sampling. The data obtained were analyzed with SPSS ver24 32bit for windows to see a comparison of MDA levels between smokers and nonsmokers. Results: From the analysis results data obtained in male smokers 0.503 ± 0.108, while nonsmokers 0.190 ± 0.047. Based on the results seen that MDA levels of salivary male smokers are higher than male nonsmokers with p value = 0.001. Conclusion: Increased levels of MDA can be found in smokers with the influence of smoking behavior conducted in men aged 45-59 years. This can be proven by the P value 0.001 that shows these results significantly, where there is a difference between MDA levels in smokers and nonsmokers.